2015
DOI: 10.37856/bja.v80i1.1411
|View full text |Cite
|
Sign up to set email alerts
|

ASPECTOS NUTRICIONAIS DE Ceraeochrysa cincta SCHNEIDER, 1851 (NEUROPTERA, CHRYSOPIDAE) EM DIFERENTES PRESAS

Abstract: ASPECTOS NUTRICIONAIS DE Ceraeochrysa cincta SCHNEIDER, 1851 (NEUROPTERA, CHRYSOPIDAE) EM DIFERENTES PRESAS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…However, other authors have associated these species as predators of coccoids. De Bortoli et al (2005) demonstrated that this species had potential as a control agent of Selenaspidus sp. (Hemiptera: Diaspididae) and Coccus sp.…”
Section: Neuropteramentioning
confidence: 99%
See 1 more Smart Citation
“…However, other authors have associated these species as predators of coccoids. De Bortoli et al (2005) demonstrated that this species had potential as a control agent of Selenaspidus sp. (Hemiptera: Diaspididae) and Coccus sp.…”
Section: Neuropteramentioning
confidence: 99%
“…Ceraeochrysa paraguaria (Navás) preferred the armored scale Selenaspidus sp. (De Bortoli & Murata 2006), and Ceraeochrysa cincta (Schneider) was observed on colonies of Leptococcus eugeniae (Miller & Denno) (as Plotococcus eugeniae) (Hemiptera: Pseudococcidae) (Eisner & Silberglied 1988). Eight species of Chrysopidae were associated with M. hirsutus, but of these only Chrysoperla carnea (Stephens) is known in Brazil (Chong et al 2015).…”
Section: Neuropteramentioning
confidence: 99%
“…With other food, the 1 st , 2 nd , and 3 rd instars had lower survival, with ranges of 70.0 to 75.0%, 60.0 to 70.0%, and 55.0 to 70.0%, respectively. Research on lacewings fed with S. cerealella eggs have found high rates of viability, indicated that they can be used for mass production of this predator in the laboratory, a fact highlighted by Fonseca et al (2001), De Murata (2007), andDe Bortoli et al (2009). However, the fact that C. cubana has a high survival rate when consuming citrus blackflies, except when the food is in the egg stage, shows the potential of this prey to be used as the diet of this predator.…”
Section: Resultsmentioning
confidence: 94%
“…The food in the immature stage of predators affects their rate of growth, development time, weight, survival, behavior, and reproductive success (PARRA, 1991). Differences in these biological parameters of the predator from different prey has been found by Almeida et al (2009) for Ceraeochrysa claveri Navás (Neuroptera: Chrysopidae), De Bortoli et al (2009) for Ceraeochrysa cincta Schneider (Neuroptera: Chrysopidae), and De Bortoli and Murata (2011), for Ceraeochrysa paraguaria Navás (Neuroptera: Chrysopidae).…”
Section: Introductionmentioning
confidence: 94%
“…Con este fin en mira fueron seleccionadas cinco especies de controladores biológicos: 1) Ceraeochrysa cincta (Neuroptera: Chrysopidae) es una especie distribuida desde Estados Unidos de América hasta Argentina, incluyendo las Islas Galápagos en América del Sur (TAUBER; DE LEÓN, 2001). Se le encuentra asociada a diversos artrópodos plaga en diferentes sistemas agrícolas y presenta un gran potencial para la cría masiva para ser usada en programas de control biológico (LÓPEZ et al, 1999;BORTOLI et al, 2005;RAMÍREZ et al, 2007). 2) Chrysoperla asoralis (Neuroptera: Chrysopidae) es una especie depredadora Neotropical usada en Europa, Norteamérica, México, Colombia y Perú para el control de plagas en campo abierto y en invernadero en el cultivo de espárrago, en hortalizas y en frutales (GONZÁLEZ; REGUILLÓN, 2002;GONZÁLEZ et al, 2009).…”
unclassified